Anomalous biliary and vascular anatomy—Potential pitfalls during cholecystectomy. Issue 8 (22nd May 2017) - Grimes, N.; Mark, D.; McKie, L.; Scoffield, J.; Kirk, G.; Taylor, M.; Diamond, T.
Abstract : Laparoscopic cholecystectomy is usually a low‐risk procedure associated with a short stay and a low rate of conversion to open surgery. Complications are sometimes associated with anomalous vascular or biliary anatomy. Outlined below are the variations in vascular and biliary anatomy which may result in complications either due to involvement in the inflammatory process or inadvertent division during dissection. Clin. Anat. 30:1103–1106, 2017. © 2017 Wiley Periodicals, Inc.